Kualitas Pelayanan Publik dalam Pembuatan Paspor di Kantor Imigrasi Kelas II Non TPI Banggai - Revalia H. Maedja; Zuchri Abdussamad; Yakob Noho Nani; Ismet Sulila; Irawaty Igirisa (Perspektif Administrasi Publik dan hukum, 2026)
One of the crucial elements in government operations is the quality of public services, particularly passport services at the Class II Non-TPI Banggai Immigration Office. The purpose of this study was to evaluate the quality of public services using the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. This is a qualitative study using a descriptive approach. Informants, consisting of employees and service users, were observed, recorded, and interviewed as part of the data collection process. The results indicate that public services at the Class II Non-TPI Banggai Immigration Office are not yet optimal. In terms of tangible dimensions, there are still limitations in facilities, such as waiting rooms and the number of seats available to the public. In terms of trust, there are inconsistencies in service times and the ability of officers to operate technology-based systems. In terms of responsiveness, officers are not fast enough in providing services and responding to public complaints, especially during busy times. In terms of trust, the certainty of passport processing times and the clarity of information are still not fully consistent, so there is still room for complaints. In terms of empathy, attitude, communication, and attention to the public, there is still a lack of clear alignment and harmony among officers. This study concludes that the quality of public services at the Class II Non-TPI Banggai Immigration Office still needs to be improved through improvements to facilities and infrastructure, increased officer competence, optimization of the service system, and strengthening professional attitudes in providing services to the public.